(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The research aims to apply time driven Activity-based budgeting (TDABB) in health service units due to the weakness of the budgeting system in them, as it relies on traditional budgets and systems, and after studying the reality of Al-Hakim General Hospital for the Surgical Department, and relying on visits, personal field interviews, and collecting information from the documents that were obtained. On her from the hospital. The research reached conclusions, the most important of which is that applying TDABB technology leads to obtaining accurate information, revealing the cost of exploited and unexploited energy, and saving time and cost. One of the most important recommendations is developing the government accounting system by introducing modern cost management techniques, including TDABB, to determine the costs of the service provided, and spreading the culture of change and development with modern techniques to control costs and effective oversight of human resources and others.